Biodiversity and ethnobotanical potentials of plant species of University of Agriculture Makurdi Wildlife Park and Ikwe Games Reserve, Benue State, Nigeria (2009)
Plant biodiversity and ethnobotanical potentials of University of Agriculture Makurdi (UAM) Wildlife Park and Ikwe Games Reserve, Benue State, Nigeria, were investigated in this study. Floristic survey was conducted in the two reserves using stratified sampling technique based on the three identified microhabitats in each of the reserves. Nine plots measuring 25 m x 25 m were laid in each of the reserves to survey trees and shrubs with diameters at breast height (dbh) 5 cm and above. Within each plot, 5 sub-plots of 1 m × 1 m were established to assess plants below 5 cm dbh. Participatory ethnobotany and interview were used for the ethnobotanical survey. Seventy-one valuable species belonging to 39 families were identified. Ninety-three percent of these have more than one use; categories with medicinal uses topping the list (48%). Other uses include: wood (35%) and food (17%). Harvesting techniques in many of the species were intensive and destructive. It is suggested that harvesting of plant products in these reserves be controlled through monitoring and enlightenment.